Does respiratory drive modify the cerebral vascular response to changes in end‐tidal carbon dioxide?. Issue 9 (19th July 2019) - Ogoh, Shigehiko; Suzuki, Kazuya; Washio, Takuro; Tamiya, Kazuki; Saito, Shotaro; Bailey, Tom G.; Shibata, Shigeki; Ito, Go; Miyamoto, Tadayoshi
Abstract : New Findings: What is the central question of this study ? There is an interaction between the regulatory systems of respiration and cerebral blood flow, because the mediator (CO2 ) is the same for both physiological systems. We examined whether the traditional method for determining cerebrovascular reactivity to CO2 is modified by changes in respiration. What is the main finding and its importance ? Cerebrovascular reactivity was modified by voluntary changes in respiration during hypercapnia. This finding suggests that an alteration in the respiratory system may result in under‐ or overestimation of cerebrovascular reactivity determined by traditional methods in healthy adults. Abstract: The cerebral vasculature is sensitive to changes in the arterial partial pressure of CO2 . This physiological mechanism has been well established as a cerebrovascular reactivity to CO2 (CVR). However, arterial CO2 may not be an independent variable in the traditional method for assessment of CVR, because the cerebral blood flow response is also affected by the activation of respiratory drive or higher centres in the brain. We hypothesized that CVR is modified by changes in respiration. To test our hypothesis, in the present study, 10 young, healthy subjects performed hyper‐ or hypoventilation to change end‐tidal CO2 ( P ET, C O 2 ) with different concentrations of CO2 in the inhaled gas (0, 2.0 and 3.5%). We measured middle cerebral artery mean blood flow velocity by transcranial Doppler ultrasonography to identify the cerebral blood flow response to change in P ET, C O 2 during each set of conditions. In each set of conditions, P ET, C O 2 was significantly altered by changes in ventilation, and middle cerebral artery mean blood flow velocity changed accordingly. However, the relationship between changes in middle cerebral artery mean blood flow velocity and P ET, C O 2 as a response curve of CVR was reset upwards and downwards by hypo‐ and hyperventilation, respectively, compared with CVR during normal ventilation. The findings of the present study suggest the possibility that an alteration in respiration might lead to under‐ or overestimation of CVR determined by the traditional methods. Abstract :